E-216 The effect of omeprazole on patients taking clopidogrel after flow diverter device placement. (4th August 2020) - Catapano, J; Fredrickson, V; Wakim, A; Lundberg, J; Hendricks, B; Baranoski, J; Cole, T; Wilkinson, D; Majmundar, N; Albuquerque, F; Ducruet, A
Abstract : Background: Omeprazole is a common proton pump inhibitor (PPI) that interferes with clopidogrel hepatic activation, potentially reducing its platelet inhibition efficacy. In the cardiovascular literature, omeprazole has been reported to increase P2Y12 reactivity levels and may lead to adverse cardiovascular outcomes in patients treated with drug eluting stents following cardiac catheterization. However, literature on omeprazole taken in association with clopidogrel is lacking in the neuroendovascular literature. We hypothesized that patients taking omeprazole would exhibit higher PRU levels and increased complications following treatment with a flow diverter device (FDD). Methods: All patients with a FDD placement for an intracranial aneurysm at a large tertiary institution from January 1st, 2015 to December 31st, 2018 were retrospectively analyzed. Inclusion criteria included 1) documented clopidogrel administration, 2) available P2Y12 levels, and 3) thorough documentation of administration of other medications including omeprazole. Outcomes analyzed included ischemic stroke on MRI and FDD stenosis on follow-up angiography. Results: Out of a total of of 138 patients that met the inclusion criteria, 16 (12%) were taking both omeprazole and clopidogrel. The average age for the omeprazole patients was significantly higher than those not taking omeprazole[69(±10) vs 57(±14) (p=0.001)]. A significantly higher P2Y12 reactivity (decreased platelet inhibition) was observed in patients taking omeprazole (PRU=250) versus those not taking omeprazole (PRU=110) (p<0.001). Furthermore, a higher number of patients were found to have a P2Y12 level >180 PRU in the omeprazole (N=14, 88%) vs no omeprazole (N=24, 20%) patients (p<0.001, OR 29; 95% CI 6–134). There were no significant differences in the rates of ischemic strokes, FDD stenosis, or hemorrhagic complications between the two groups. Conclusion: Omeprazole significantly increases the P2Y12 reactivity levels in intracranial aneurysm patients on clopidogrel treated with a FDD. However, omeprazole did not increase the risk of ischemic events and/or device stenosis. Nonetheless, given the significant association between omeprazole and decreased clopidogrel efficacy, omeprazole should not be administered to neuroendovascular patients treated with a FDD taking clopidogrel. Disclosures: J. Catapano: None. V. Fredrickson: None. A. Wakim: None. J. Lundberg: None. B. Hendricks: None. J. Baranoski: None. T. Cole: None. D. Wilkinson: None. N. Majmundar: None. F. Albuquerque: None. A. Ducruet: None.